Diagnosis and management of anaphylaxis in children - Pasquale Comberiati; Francesca Innocenti; Roberto Bernardini; Massimo Landi; Alberto Martelli; Diego Peroni (Elsevier, 2024)
Anaphylaxis is a potentially life-threatening event that requires prompt recognition and management. Although the frequency of hospitalization for anaphylaxis in children has increased in the last decades in several countries, trends of fatal anaphylaxis remained stable. Teenagers and young adults show a higher risk of near-fatal and fatal food-induced anaphylaxis. This short review addresses current knowledge of the epidemiology, diagnosis, and treatment of anaphylaxis in pediatric age.